PENGARUH KOMPENSASI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN CV. DAYUH SINI DENPASAR TIMUR - I Made Agus Sudiatmike; Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati (EMAS, 2023)
This study aims to determine the effect of compensation, work motivation and job satisfaction on employee performance at CV. Dayuhsini, East Denpasar. This study took 50 respondents on the CV. Dayuhsini, East Denpasar. The data were analyzed using multiple linear regression analysis techniques to answer the problem formulation with the help of the SPSS (Statistical Package Social Science) program. 25. The results of testing the hypothesis show that the variables: 1) compensation has a positive and significant effect on employee performance, 2) work motivation has a positive effect. and significant effect on employee performance and 3) job satisfaction has a positive and significant effect on employee performance.